Analysis of Federal Government Budgetary Allocation for Staff Ratio between Teaching and Support Staff of Federal Universities in North-Central Nigeria - Azi, Augustine Sambo (NIU Journal of Social Sciences, 2019)
The purpose of this study was to analyse the influence of federal government budgetary allocation for staff ratio between teaching and support staff in federal universities in North-Central Zone of Nigeria. This is because there are limited and unstructured data that show pattern and extend of use of universities funds for the ratio between teaching and support staff. The study specifically examined the adequacy of federal government budgetary allocation to universities and its influence on the ratio of teaching staff and support staff in universities in North-Central Zone of Nigeria. Apart from extracting relevant Documents relating to budgetary allocations from the sampled universities, a descriptive research design was employed and data was collected from 5 out of 7 university Vice-Chancellors, 101 out of 254 bursary staff, 437 out of 2,912 lecturers and 50 out of 84,304 students from the five sampled federal universities. Both qualitative and quantitative research approaches were adopted in this study. The research instruments employed for data collection were questionnaires for bursary staff and lecturers, interview guide for university Vice-Chancellors, and Focus Group Discussion Guide for university students. Both descriptive and inferential statistics were employed to analyze the data. They were subjected to reliability and validity tests and found to be valid and reliable for the study. The findings from the field and documents showed that as a result of inadequate funding to universities, the ratio between support and teaching staff was low, with the universities having an average ratio of 2:1.This implies that teaching staff are not adequately supported with negative consequences on their performance. The implication of this finding on the study is that Nigerian universities will not only be able to achieve their developmental priorities, they will also not be able to assist the Nigerian government achieve the Vision 20:2020 development plan.  The study recommended among others that budgetary allocations to universities should be increased by government so that university administrators can utilize it for the recruitment of teaching and support staff. This will enhance a healthy ratio between teaching and support staff in universities.